2010
DOI: 10.1007/s00421-010-1423-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasma adiponectin concentration is associated with the average accelerometer daily steps counts in healthy elderly females

Abstract: This study is aimed to evaluate whether circulating adiponectin concentration is associated with physical activity (PA) level in healthy older females. To date, daily PA in older adults (> or = 65 years) has primarily relied on self-report. This study used accelerometry, which objectively measured minute-by-minute movement to assess PA volume and intensity performed by elderly females. In addition, body composition, leptin and insulin resistance values were measured to assess the influence of these parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Although VO 2max is not higher in PO compared with C subjects, the observed higher energy expenditure implies a higher level of daily physical activity, which is known to increase plasma adiponectin levels. 47,48 Previous studies have reported adipose tissue hyperplasia in the PO state, 49 and it is possible that this may also influence the fasting basal adiponectin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although VO 2max is not higher in PO compared with C subjects, the observed higher energy expenditure implies a higher level of daily physical activity, which is known to increase plasma adiponectin levels. 47,48 Previous studies have reported adipose tissue hyperplasia in the PO state, 49 and it is possible that this may also influence the fasting basal adiponectin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity was associated with changes in body weight or body fat which will further affect insulin sensitivity (7). Thus, increased physical activity specifically those with moderate to high intensity may increase adiponectin (8)(9)(10)(11)(12)(13)(14)(15)(16) and decrease leptin levels (8-11, 13, 17-20).…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…An accelerometer was used to measure physical activity in all six studies included. Plasma adiponectin and leptin were mostly analysed by using enzyme-linked immunosorbent assay (ELISA) (10, 31) and radio immune assay (RIA) (8,9,17,27) daily PA in older adults (> or = 65 years. The intra-assay coefficient of variation (CV) was in the range from 3% to 10% for adiponectin while 10% for leptin.…”
Section: Relationship Between Physical Activity/exercise and Adipokinmentioning
confidence: 99%
“…Regarding the effect of exercise on hormone levels related to nutrient metabolism, exercise increased adiponectin and decreased leptin in blood (Table 1), leading to enhanced insulin sensitivity, as in humans [36,37]. The altered levels of blood adiponectin and leptin cannot be explained by gene expressions in WAT because exercise did not significantly influence the expression level of adiponectin and leptin in WAT (data not shown).…”
Section: Discussionmentioning
confidence: 98%